Accelerated differentiation of human pluripotent stem cells into neural lineages via an early intermediate ectoderm population. (19th August 2020) - Walsh, Patrick; Truong, Vincent; Nayak, Sushmita; Saldías Montivero, Marietta; Low, Walter C.; Parr, Ann M.; Dutton, James R.
Abstract: Differentiation of human pluripotent stem cells (hPSCs) into ectoderm provides neurons and glia useful for research, disease modeling, drug discovery, and potential cell therapies. In current protocols, hPSCs are traditionally differentiated into an obligate rostro‐dorsal ectodermal fate expressing PAX6 after 6 to 12 days in vitro when protected from mesendoderm inducers. This rate‐limiting step has performed a long‐standing role in hindering the development of rapid differentiation protocols for ectoderm‐derived cell types, as any protocol requires 6 to 10 days in vitro to simply initiate. Here, we report efficient differentiation of hPSCs into a naive early ectodermal intermediate within 24 hours using combined inhibition of bone morphogenic protein and fibroblast growth factor signaling. The induced population responds immediately to morphogen gradients to upregulate rostro‐caudal neurodevelopmental landmark gene expression in a generally accelerated fashion. This method can serve as a new platform for the development of novel, rapid, and efficient protocols for the manufacture of hPSC‐derived neural lineages. Abstract : Efficient conversion into primal ectoderm by treatment with BGJ398 and LDN193189 accelerates neural induction in human pluripotent stem cells.